The Mesozoic Hydrocarbon Source Rock Potential of Singkawang Basin, West Kalimantan - Suyono Suyono; M.H. Hermiyanto Zajuli (Jurnal Geologi dan Sumberdaya Mineral, 2018)
The Singkawang Basin is one of  Mesozoic Basins in Western Indonesia that located in West Kalimantan. The Mesozoic Singkawang Basin is expected to have potential resources for conventional as well as non-conventional hydrocarbons. Several new concepts of oil and gas exploration may be defined in this basin including volcanic, basement fracture and Mesozoic sedimentary reservoirs.  The Singkawang Basin is a basin filled with sedimentary rocks that may have hydrocarbon potential  This basin has not been many studied by previous researchers. The aim of this research is to determine the potential of fine grained sedimentary rocks in the Singkawang Basin as the source rock of hydrocarbons. The TOC and Rock-Eval Pyrolysis (REP) analysis results from 69 fine-grained sedimentary rock samples concluded that the Sungaibetung Formation has a rich organic material ranging from 0.95 – 2.84%, while the Banan Formation ranges from 0.42 – 2.41%, the Pedawan Formation ranges from 0.27-2.29%, and the Kayan Formation ranges from 0.41 – 1.82%. The hydrogen index (HI) value of < 150 mg HC/g TOC and S2/S3 ratio value of < 3 indicates that some fine-grained sedimentary rocks of the Mesozoic Singkawang Basin have a tendency as a dry gas producer kerogen type and classified as a lean organic matter. The sedimentary rocks of the Singkawang Basin can be interpreted as gas source rocks that have entered an over mature stage. The Triassic to Oligocene fine -grained sedimentary rock indicates a good organic material. Moreover, the Sungaibetung Formation consists of very good organic material and tend to indicate hydrocarbons source rocks potential.Keywords: Mesozoic, source rocks, hydrocarbons, West Kalimantan